2020
DOI: 10.1177/1524839919896787
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Features of Culinary Nutrition Education That Drive Behavior Change: Frameworks for Research and Practice

Abstract: Evidence of the benefits of culinary nutrition education is growing in the literature. Culinary nutrition education programs are naturally experiential, social, skills-based, and effective in improving nutrition-related beliefs, knowledge, and behaviors. In this article, we explore a set of motivational experiences in culinary nutrition education that have been identified as “drivers” of behavior change. These drivers emerged from 20 years of implementation and evaluation of hands-on cooking programs across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…The mean difference for self-efficacy for increasing intake of vegetables was 7.2 (6.0−8.4), for self-efficacy for eating more fruits, it was 5.4 (4.3−6.5), for self-efficacy for increasing consumption of whole grains, it was 4. 20 may have been more likely to occur in this semester-long intervention that offered enough practice opportunities for advancement of skills. The study findings are consistent with those from a systematic review that highlighted the positive impact of cooking classes on diet and cooking confidence 21 ; however, most participants in the studies included in that review were middle-aged or older adults with a clinical condition.…”
Section: Resultsmentioning
confidence: 97%
“…The mean difference for self-efficacy for increasing intake of vegetables was 7.2 (6.0−8.4), for self-efficacy for eating more fruits, it was 5.4 (4.3−6.5), for self-efficacy for increasing consumption of whole grains, it was 4. 20 may have been more likely to occur in this semester-long intervention that offered enough practice opportunities for advancement of skills. The study findings are consistent with those from a systematic review that highlighted the positive impact of cooking classes on diet and cooking confidence 21 ; however, most participants in the studies included in that review were middle-aged or older adults with a clinical condition.…”
Section: Resultsmentioning
confidence: 97%
“…The preparation and cooking domain of food literacy appears to be the active ingredient for individuals using food literacy to improve their dietary intake. Fredericks et al discussed the ten experiential features of culinary or cooking programs that instigate behavioural changes based on the experience of nutrition educators [26]. At the beginning of the FSA program, 68% (n = 1605) of participants rated themselves as being able to cook almost anything or cook a wide variety of meals; at the follow-up, participants improved the perception of their skills [20].…”
Section: Discussionmentioning
confidence: 99%
“…short-term intervention such as this. We attribute the success of this intervention in large part to its practical and interactive nature, which the literature also nds to be the most effective method of nutrition education 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions aimed at addressing doctors' nutritional knowledge gaps are becoming increasingly common in the medical education and healthcare landscapes. The most successful nutrition education interventions, recent literature has found, are practical and emphasize skill development instead of mere knowledge acquisition 33,34 . This nding is congruent with recent pedagogical research that has demonstrated the superiority of active learning in engagement and content mastery compared to lecturing alone, particularly in the science, technology, engineering, and mathematics (STEM) elds [35][36][37] .…”
mentioning
confidence: 99%